Survival rate and its predictors in HIV patients: A 15-year follow-up of 3030 patients - Zahra Naghibifar; Alireza Janbakhsh; Mansour Sajadipour; Maryam Emadzadeh; Armin Naghipour; Amirhossein Sahebkar (Elsevier, 2024)
Background: The high prevalence of HIV infection and the deaths caused by it is one of the challenges for the healthcare systems throughout the world. In this study, we analyzed the survival of people living with HIV and co-infections, and related factors. Methods: This retrospective cohort study was performed on 3030 people living with HIV admitted to Imam Khomeini Behavioral Disease Counseling Center, Tehran, Iran, during 2004-2018. Required data were obtained from the individuals' files. Kaplan Meier diagrams and Log-rank tests were used to assess the relationship between different factors and survival. In addition, Cox regression analysis was performed to determine the effective factors in HIV mortality. Data were analyzed using STATA software, version 14. Results: The mean age of studied population was 43.2 ± 9.5 [years] and 77.3 % were male. Among the subjects, 3.2 % were infected with hepatitis B, 31.5 % with hepatitis C, and 13.9 % with Tuberculosis (TB). One, five, ten, and fifteen-year survival rates were 97.0 %, 93.0 %, 86.0 %, and 54.0 %, respectively. The mean survival time was 154.2 ± 0.9 months. Age more than 35, history of imprisonment, Unsafe sexual behavior, TB, and hepatitis C are independently associated with death in people living with HIV (p < 0.05). Conclusion: The survival of people living with HIV in the present study was in the favorable range compared to previous studies. However, co-infection with hepatitis C was associated with reduced survival of the subjects in this study. Therefore, it is suggested to detect and then prevent and control HCV co-infection to increase the survival of subjects.